Cloure els ulls per veure el món. Sobre ulls i cegueses en la poesia catalana contemporània - Perarnau Vidal, Dolors (Studia Romanica Posnaniensia, 2025)
This work examines the critique of language that contemporary Catalan poetry has been carrying out since the seventies and how it has deepened the abyss between word and world. The analyse will be based on the grounds of one aphorism from Søren Kierkegaard’s Diapsalmata and the critique of the deception and illusion inherent in all form of discourse, whether philosophical, scientific, or literary, with examples from Magritte, Hofmannsthal, and, especially, contemporary Catalan poets, from Gimferrer to Gemma Gorga through Víctor Sunyol, Antoni Clapés, Anna Montero, Camps Mundó, or j. l. badal, among others. This work concludes that, while knowing and expressing the world may have become impossible, poetry and art still offer a space in which this impossibility can be experienced. In doing so, both help us to avoid falling into the trap of language’s false promises.